2019
DOI: 10.9788/tp2019.2-06
|View full text |Cite
|
Sign up to set email alerts
|

Job Crafting Interventions: Systematic Review

Abstract: Job crafting is proactive bottom-up job redesign to optimize person-job fi t. A job crafting intervention is any training or method designed to stimulate or develop job crafting behaviors in employees. This paper systematically reviews research examining the eff ects of job crafting interventions and identifi es their tendencies and gaps. A search was conducted in PsycINFO, Academic Search Premier, Web of Science, and SciELO using the key terms job crafting and interventions in databases available from 2007 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
0
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 27 publications
4
22
0
4
Order By: Relevance
“…Second, regarding job crafting, the results of this research corroborate the consistent findings of the impacts on well-being (Demerouti, 2014;Devotto & Wechsler, 2019;Devotto et al, 2017;Lazazzara et al, 2020;Tims et al, 2013;van Wingerden et al, 2017;Wang et al, 2016;Wrzesniewski & Dutton, 2001;Wrzesniewski et al, 2013). Moving beyond the findings already identified in the literature, the present study revealed that, in a remote work context, work achievement is a dimension of well-being particularly sensitive to proactive behaviors of changing the work itself to align it to personal values and interests.…”
Section: Confirmatory Validation Of the Prediction Modelsupporting
confidence: 79%
See 1 more Smart Citation
“…Second, regarding job crafting, the results of this research corroborate the consistent findings of the impacts on well-being (Demerouti, 2014;Devotto & Wechsler, 2019;Devotto et al, 2017;Lazazzara et al, 2020;Tims et al, 2013;van Wingerden et al, 2017;Wang et al, 2016;Wrzesniewski & Dutton, 2001;Wrzesniewski et al, 2013). Moving beyond the findings already identified in the literature, the present study revealed that, in a remote work context, work achievement is a dimension of well-being particularly sensitive to proactive behaviors of changing the work itself to align it to personal values and interests.…”
Section: Confirmatory Validation Of the Prediction Modelsupporting
confidence: 79%
“…The relationship between job crafting and well-being or correlated variables have been consistently described in the literature (Demerouti, 2014;Devotto & Wechsler, 2019;Devotto et al, 2017;Lazazzara et al, 2020;Tim et al, 2013;van Wingerden et al, 2017;Wang et al, 2016;Wrzesniewski & Dutton, 2001;Wrzesniewski et al, 2013). A literature review carried out by Wang et al (2016) indicates a few immediate impacts of job crafting, such as engagement at work, work satisfaction, and performance, and long-term effects, such as the meaning of work and identification with work.…”
Section: Job Craftingmentioning
confidence: 80%
“…This study suggests that job crafting can indeed be an effective and valuable tool for maintaining and even enhancing work engagement when facing changes. A vast amount of previous research has shown that job crafting behavior can be learnt, and many job crafting interventions have been conducted in recent years [79,80]. However, because of the previous indications of the negative effects of avoidance job crafting, interventions have sometimes focused more on optimizing hindering demands, such as aiming to work more efficiently [81], than decreasing them, and some studies have excluded avoidance job crafting strategy altogether from the content of their interventions [82,83].…”
Section: Theoretical and Practical Implicationsmentioning
confidence: 99%
“…A maneira como uma demanda é percebida e abordada, a depender dos recursos disponíveis, pode -quando em situações desfavoráveis -produzir efeitos distintos, como engajamento em atividades consideradas desafiadoras ou desgaste (Heckenberg et al, 2018). Assim, o modelo JD-R tem sido aplicado em estratégias de job crafting a fim de contribuir com o redesenho do trabalho (Devotto & Wechsler, 2019).…”
Section: Mots-clés : Psychologie Du Travail ; Stress ; Maternité ; Ph...unclassified